Analisis Filsafat Dakwah: Inovasi Kebijakan Revolusi Akidah Dan Akhlak Bagi Generasi Z Dan Alpha - Satriyo, Bagus; Falach, Ghulam; Hidayah, Islamiati (Faculty of Social and Political Science, 2024)
The decline in manners and morals among Generation Z and Alpha, largely due to technology dependence and insufficient religious education, necessitates urgent intervention. This research investigates innovative da'wah policies aimed at enhancing the faith and morals of youth, particularly through the Kediri City Great Mosque Youth Organization. Utilizing qualitative methods such as interviews and observations, the study incorporates various philosophical perspectives, including idealism and humanism. Findings indicate that leveraging social media and AI technology, along with positive adult role models, significantly boosts moral understanding among youth. Specifically, the research highlights impressive engagement rates for example online learning, AI applications, and organizational da'wah activities. These results underscore the critical need for a digital approach to faith and moral education, emphasizing collaboration among families, organizations, and communities to cultivate integrity and strong moral character in future generations.